TEACHING SPEAKING BY USING ELICITATION TECHNIUE TO THE EIGHTH GRADE STUDENT OF SMP NEGERI 2 LUBUKLINGGAU - Nova Gultom; Sastika Seli; Agus Triyogo (JURNAL LINER (Language Intelligence and Educational Research), 2022)
ABSTRACTThe aim of the research was to find out whether or not it was significantly effective to teaching students speaking by using elicitation technique to the eighth grade students of SMP Negeri 2 Lubuklinggau. The sample of the research was 38 students taken from class of Eighth-five. In this research, the researcher used pre-experimental research with one group of pre-test and post-test. Based on the collecting the data by used oral test, the result of the research indicated that elicitation technique was significantly effective to improve students speaking at eighth students. It could be seen from the score students in pre-test and post-test. The average of student’s score in pre-test was 66 achieve by one students and 100% failed in test, meanwhile the students’ average score in post-test was 88 achieve by 3 students and 27 students passed in test or 71%. In addition, the result of paired t-test was that tobtained was 13.24 and ttable was 1.70. it mean tobtained was higher than ttable (13.24 ≥ 1.70). Alternative (Ha) was accepted and it was significantly effective to teach speaking by using elicitation technique to the eighth grade students at SMP Negeri 2 lubuklinggau.Key words: Teaching Speaking, Elicitation Technique